Levodopa/carbidopa intestinal gel infusion in advanced Parkinson's disease: a 7‐year experience. (7th December 2013) - Zibetti, M.; Merola, A.; Artusi, C. A.; Rizzi, L.; Angrisano, S.; Reggio, D.; De, C.; Rizzone, M.; Lopiano, L.
<x xml:space="preserve">Abstract</x> Background and purpose Levodopa/carbidopa intestinal gel (LCIG) infusion is nowadays becoming an established therapeutic option for advanced Parkinson's disease (PD) patients with fluctuating symptoms unresponsive to conventional oral treatment. As the implementation of LCIG therapy is increasing, there is a need for safety and efficacy data from current clinical practice. Methods All PD patients treated with LCIG at our centre over a 7‐year period were analysed to determine the duration of treatment, retention rate, reasons for discontinuation, LCIG efficacy in motor complications, modifications of concomitant therapy and adverse events. Results Of the 59 patients, seven subjects (12%) died of causes unrelated to LCIG infusion and 11 patients (19%) discontinued therapy prior to the cut‐off date. Duodopa improved motor complications and over 90% of patients reported an improvement in their quality of life, autonomy and clinical global status. The most common adverse events were dislocation and kinking of the intestinal tube. Conclusions LCIG infusion is effective for the long‐term treatment of advanced PD patients and exerts a positive and clinically significant effect on motor complications with a relatively low dropout rate.